MAKNA PENTING TOL LAUT BAGI PEMBANGUNAN NASIONAL INDONESIA PADA MASA PEMERINTAHAN JOKO WIDODO – JK - Hendra Maujana Saragih (Jurusan Ilmu Hubungan Internasional, 2017)
The toll of the sea is a Jokowi-JK strategy to revive Indonesia as the era of the ancient empires in the days before Indonesia's independence. Jokowi-JK carrying the idea because 2/3 of Indonesian territory is sea. Indonesia is an archipelagic state where the distance between one island with the other is far a part. So that the price difference between the Java and the eastern part of Indonesia will be much different, especially in papua. This is due to the high transportation costs. Therefore, with the existence of the sea toll, the human resources will be awakened because goods will be well cycled also Will be a lot of business opportunities which will be opened later. The research method used is descriptive analysis case study approach is to look at the phenomenon of existing problems in the field with respect to issues that are examined. The data obtained during the research will processed, analyzed and further processed on the basis of theoretical theory that has been studied. The conclusion that the sea toll that Jokowi-JK must be implemented soon.